PERANCANGAN SISTEM STANDARISASI DESA WISATA KABUPATEN BANTUL DENGAN MODEL SISTEM PENGUKURAN KINERJA BALANCED SCORECARD GUNA PENGUATAN INDUSTRI PARIWISATA DAERAH - Zabidi, Yasrin; Suhardiwamo, Suhardiwamo (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
Bantul regency until now has approximately 36 villages wisata. Standarisasi tourist village needs to be done, which is the standard tourist village which is categorized as an embryo, develops, and advanced. These standards can be used by Disbudpar to determine work programs such as mentoring programs, counseling, training for rural tourism in the category or the developing embryo. One standardized assessment instrument is the assessment of performance against a tourist village. Therefore, in this study, researchers are trying to design a system of standardization of the tourist village of Bantul model performance measurement system balanced scorecard that includes the identification of performance criteria, strategic objectives, determining indicators of performance, the determination method / means of performance measurement precise, systematic and easy to use, as well as the design of performance reporting. The design activity in this study is divided into four phases, namely: the initial phase of the study and formulation of the problem, the design phase, the phase of analysis and conclusion phase. Early research phase and the formulation of the problem include the formulation of the problem and determine the research objectives. Design phase includes the design process performance measurement system with Balanced Scorecard method which includes the establishment of strategic objectives, the establishment of performance indicators (key performance indicators / KPIs), target setting and action plans, draft worksheet performance measurement methods Omax and draft reporting of performance-based website. Phase analysis includes analysis of balanced scorecard performance measurement system that includes analysis perspective, the analysis of strategic objectives, KPI analysis and analysis of the strategy map. Phase conclusions include conclusions from the findings and suggestions.Â From the research performance based on four perspectives of the balanced scorecard, namely financial, customer, internal business processes, learning and growth. Strategic objectives that form there are 10 and there are 24 KPI KPI formed. Besides of this study the formation worksheet Omax performance measurement method, so that can know the value of each performance indicator of performance and total performance in a particular period.